Retracted: Comparative study between proximal femoral nail and dynamic hip screw with trochanteric stabilizing plate in unstable intertrochantric femur fractures - Patil, Siddaram N.; Srinivas, Pandurangaiah (International Journal of Research in Orthopaedics, 2017)
The article titled, "Comparative study between proximal femoral nail and dynamic hip screw with trochanteric stabilizing plate in unstable intertrochantric femur fractures", published in the International Journal of Research in Orthopaedics, Volume 3, Issue 5, 2017, Pages 936-943, DOI: http://dx.doi.org/10.18203/issn.2455-4510.IntJResOrthop20173198 is being retracted. After the publication of the above article, one of the researchers reported that a large part of the text, clinical photographs, x-ray images and tables are plagiarized from his dissertation work. We contacted the author who could not satisfactorily respond to our queries. Since the author could not satisfactorily defend his paper, it was decided to retract the article from International Journal of Research in Orthopaedics.